The viewpoint of nanolipid vesicles (liposomes, exosomes, and microvesicles) as biosensors in medical health advances - Elham Ghazizadeh; Elham Ghazizadeh; Zahra Nasery (Frontiers in Nanotechnology, 2023)
Biosensors are of significant importance today in the rapid, sensitive, and reliable detection of biological molecules in many fields, including medicine; owing to this fact, the development of a strong and reliable diagnostic agent is a very interesting topic. Because of their unique features, among other nanomaterials, lipid-based vesicles such as liposomes, exosomes, and microvesicles represent a type of biocompatible and versatile biosensing membrane surface for rapid biomarker detection and diagnosis of diseases, enhancing the assay sensitivity and decreasing the detection limit. In this review, we have reviewed the recent diagnostic application of lipid-based vesicles as biosensing substances in both conventional and novel techniques for identifying targets, especially in medicine and biotechnology sciences. Eventually, we have highlighted several recent promising developments in a new generation of biosensors based on liposome–nanomaterial hybrids and exosomes for analyzing targets and possible further advances in the future.